Frontispiece: Recent Advances in Germanium‐Based Photoinitiator Chemistry. Issue 33 (14th June 2018) - Haas, Michael; Radebner, Judith; Eibel, Anna; Gescheidt, Georg; Stueger, Harald
Abstract : Photopolymerization has witnessed a tremendous increase of interest in the last couple of years. In this context acylgermanes were found to be highly efficient photoinitiating systems. Advances in the design and application of acylgermanes as visible‐light photoinitiators for free radical polymerization are highlighted in the Minireview article by G. Gescheidt, H. Stueger et al. onpage 8258 ff. with a strong emphasis on recently introduced tetraacylgermanes. The most common synthetic strategies are summarized along with a concise overview of the related photochemical reactivities.